From Individual to Collaborative Information Behavior - Yıldız, Hakan; Özenç Uçak, Nazan (Information World, 2014)
Information behavior is an important field, which is increasingly studied by different disciplines. It is known that the first studies conducted related with information behavior were system focused, their aim was to resolve problems of the system and the subject was approached in terms of information centers. However after 1980, the topic was tackled in terms of user/ individual. During the last decade, the focus shifted from individual information behavior to collaborative information behavior. The collaborative information behavior assists in taking ideal decisions by generating common sense through collaboration within the teams/communities. Both theoretical as well as technical studies related with this subject are still in the pre-paradigm stage. Limited numbers of models are developed with the increase of theoretical and technical studies. Factors like common platform, context, awareness, triggers, trust and their impact on the behavior are investigated in the collaborative information behavior. The variety of the interaction scenarios between man-machine (for example man-man, man-machine, man-machine-man, etc.), requires that the subject is tackled from social and/or technical perspectives and this leads to challenges in the conceptualization. Why and how the studies on information behavior, which is relatively a new field, evolved from individual information behavior to collaborative information behavior, where we stand now in terms of the studies and the opportunities presented by this field are discussed in the present study.
Keywords: Information behavior; Individual information behavior; Collaborative information seeking behavior; Information behavior models